Dynamic inflow model for hovering rotors in non-parallel ground effect - Serafini, J.; Pasquali, C.; Bernardini, G.; Gennaretti, M. (My University, 2019)
This paper presents a state-space dynamic inflow modeling method suitable for flight dynamics analysis of rotors in ground effect. Akin to the Pitt-Peters model, it relates inflow components to rotor loads as determined by a Vortex-Lattice-type numerical simulations, and may be applied to non-parallel rotor-ground configurations as well as to moving ground cases. Here, the model is identified for three flight hovering cases (far from the ground, near a parallel ground and near an inclined ground) and compared with a set of validation data, highlighting the capability of the proposed methodology to reproduce the main features of the inflow.